Determination of the influence of the phase composition of Cu-Bi coatings on the efficiency of shielding from ionizing radiation - Kadyrzhanov, K.K.; Shlimas, D.I.; Kaniukov, E. Yu.; Kaliyekperov, M.E. (of the E.A. Buketov KarU publ., 2020)
The work is devoted to the study of the efficiency of shielding the radiation exposure of heavy ions depending on the phase composition of Cu-Bi coatings. As a method of producing protective coatings, an electrochemical deposition method was used. The change in phase composition was carried out by varying the applied potentials difference during deposition. The study found that the change in phase composition leads to an increase in coating density, as a result of the dominance of the CuBi2O4 phase and an increase in the structural ordering degree. During shielding efficiency tests, it was found that the greatest decrease in the degree of crystallinity is observed for copper coatings, for which the amorphization of the structure at the maximum irradiation fluence didn’t exceed 12 %, while for coatings based on CuBi2O4 the value of amorphization was no more than 1.2 % of initial value. Amorphization and fragmentation of grains at high radiation doses leads to a decrease in the shielding efficiency, as well as an increase in the value of the deviation ΔU.
Keywords: protective coatings; shielding; ionizing radiation; heavy ions; radiation resistance